Organizational citizenship behavior in Malaysian higher educational institutions - Mohamed Idrus, Rosafizah; Idris, Khairuddin; Omar, Zoharah; Mohd Anuar, Mohd Ashraff; Ariffin, Hasfizani (Human Resource Management Academic Research Society, 2019)
Organizational citizenship behavior is a unique aspect of employee’s behaviors in the workplace which is regarded as one of the important requirements and pre requisite for organizational effectiveness. Therefore, respective top management of the organizations are driven to revisit means and ways to improve, motivate and improvise strength of each employee. Thereby, employees with organizational positive attitudes which encompasses citizenship behavior will propel the organizations in achieving effective organizational implications and outcomes in this new global economy of the twenty first century. In every organization especially in the Higher Education Institutions it is significantly imperative to examine and analyse the contribution of citizenship behavior in Malaysia context of this industry as it seen very scarce. For this reason, this study will be focusing on the level of the Citizenship Behavior, in the context of Malaysian Higher Educational Institutions which with the objective to address on the reason as to why RU staffs willing to put extra effort in undertaking their tasks beyond their job description. Data gathered from 487 staffs in five Higher Educational Institutions in Malaysia and results shown that, staffs that undertake their responsibility at the workplace above and beyond their official responsibility is normally vested with higher level in Citizenship Behavior. Suggestions from the finding and future research on this citizenship behavior were also discussed whereby it is hoped that this study can contribute towards better understanding of the concept of Organization Citizenship Behavior especially in the context of Malaysian Higher Educational Institutions.